Polyethylene glycolated PAMAM dendrimers-Efavirenz conjugates - Pyreddy, Suneela; Kumar, Pandurangan Dinesh; Kumar, Palanirajan Vijayaraj (International Journal of Pharmaceutical Investigation)
Aim: The preparation of novel PEGylated PAMAM (poly-amidoamine) dendrimers for delivery of anti-HIV drug Efavirenz is reported. Method and Materials: About 5.0 G PAMAM dendrimers are prepared by ethylene diamine core via Michael addition by divergent method. PEGylation is done by polyethylene glycol 600 using epichlorhydrin as linker. PEGylated 5.0 G PAMAM dendrimers loaded with Efavirenz (EFV) are evaluated for FTIR, DSC, SEM, drug release, and stability studies. Results and Conclusion: From the results it is proved that this method is less time consuming, inexpensive, and reproducible. Drug-release studies indicate, PEGylated 5.0 G PAMAM-EFV dendrimers have shown prolonged drugrelease property.
Keywords: Dendrimers; efavirenz; epichlorhydrin; Michael addition; PEGylation